2004
DOI: 10.1136/bmj.38042.506748.ee
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of topical capsaicin for the treatment of chronic pain

Abstract: Objective To determine the efficacy and safety of topically applied capsaicin for chronic pain from neuropathic or musculoskeletal disorders. Data sources Cochrane Library, Medline, Embase, PubMed, an in-house database, and contact with manufacturers of topical capsaicin. Study selection Randomised controlled trials comparing topically applied capsaicin with placebo or another treatment in adults with chronic pain. Data extraction Primary outcome was dichotomous information for the number of patients with abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
186
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 383 publications
(196 citation statements)
references
References 35 publications
3
186
0
7
Order By: Relevance
“…The systematic review (Mason et al 2004) and the one relevant trial it included (Keitel et al 2001) were both of high quality. The additional trial (Frerick et al 2003) was also of high quality.…”
Section: Quality Assessment Of the Evidencementioning
confidence: 99%
“…The systematic review (Mason et al 2004) and the one relevant trial it included (Keitel et al 2001) were both of high quality. The additional trial (Frerick et al 2003) was also of high quality.…”
Section: Quality Assessment Of the Evidencementioning
confidence: 99%
“…Reviews of randomised controlled trials found that topical capsaicin is superior to placebo for knee osteoarthritis and reduces pain by 50%. 19,31 In general, a concentration of 0.025% capsaicin was better tolerated than 0.075%. Withdrawal because of an adverse event was more common with capsaicin than with placebo (13% vs 3%).…”
Section: Capsaicinmentioning
confidence: 99%
“…This desensitization is dose-dependent. Capsaicin was found to be very effective in reducing the pain associated with osteoarthritis, diabetic neuropathy, and psoriasis [4,7]. Topical drug application to treat arthritic pain is thought to deliver high local drug concentration with a reduced risk of systemic side effects.…”
Section: Introductionmentioning
confidence: 99%